(untitled) (World Bulletin of Management and Law, 2025)
This article investigates the juridical pathways through which social accountability converts citizen input into publicly reasoned decisions and verifiable administrative follow-through within Uzbekistan’s architecture of public oversight. Employing doctrinal-legal and comparative-legal methods, it aligns the Constitution and core statutes on public control, openness, appeals, normative legal acts, and personal data with widely accepted procedural standards for participatory governance. Participation mechanisms are analytically situated along a thin–conventional–thick spectrum to furnish a neutral design vocabulary.